People with intellectual disabilities' experiences of primary care health checks, screenings and GP consultations: a systematic review and meta-ethnography. - Gregson, Nicola; Randle-Phillips, Cathy; Hillman, Sal (International Journal of Developmental Disabilities, 2024)
Primary care health checks, screenings and GP consultations are often the gateway for people with intellectual disabilities to access their physical and mental healthcare. For a population who experience greater levels of health difficulties alongside significant health inequality, improving care quality and access is of major importance. This meta-ethnographic, qualitative review aims to explore people with intellectual disabilities experiences of health checks, screenings and GP visits, while assessing the quality of the current literature and synthesising findings to consider clinical and research recommendations based on third order constructs. A systematic search identified 20 studies that met inclusion criteria. Quality assessment of each paper was conducted. Meta-ethnography methods were used to analyse and synthesis findings. One overarching concept was identified: Include Me, along with seven core concepts; Empowerment and Disempowerment, Communication and Interpersonal Factors, Access and Adaptations and Biased Narratives and Shifting Perspectives. Implications for practice and future direction are discussed.